2019
DOI: 10.1002/cne.24622
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tachykinin3 and related reproductive markers in the brain of the African cichlid fish Astatotilapia burtoni

Abstract: Neurokinin B, encoded by the tachykinin3 gene, plays a crucial role in regulating reproduction in mammals via KNDy neurons and interaction with GnRH. Previous work in teleost fishes has focused on hypothalamic tac3 expression for its role in reproduction, but detailed studies on extra‐hypothalamic tac3 expression are limited. Here, we identified two tac3 genes in the social African cichlid fish Astatotilapia burtoni, only one of which produces a functional protein containing the signature tachykinin motif. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…A recent anterograde labeling study indicated that LRN axons terminate mostly in aldolase C-negative areas, while BPN axons terminate in aldolase Cpositive areas . However, in previous studies, it was not clear whether a given pontocerebellar axon innervates aldol- (Table 1), and those in the mouse (83.9%) were slightly lower (Biswas et al, 2019). Whether such simple correlation of a single mossy fiber axon to aldolase C expression pattern is generalized to other mossy fiber axons partly remains a question, since single neurons innervate both aldolase C-positive and -negative bands in some mossy fiber systems such as external cuneate neurons (Ji & Hawkes, 1994) and spinocerebellar neurons (Luo et al, 2018).…”
Section: Projection Of Single Bpn Axons To Aldolase Cpositive Compamentioning
confidence: 85%
See 4 more Smart Citations
“…A recent anterograde labeling study indicated that LRN axons terminate mostly in aldolase C-negative areas, while BPN axons terminate in aldolase Cpositive areas . However, in previous studies, it was not clear whether a given pontocerebellar axon innervates aldol- (Table 1), and those in the mouse (83.9%) were slightly lower (Biswas et al, 2019). Whether such simple correlation of a single mossy fiber axon to aldolase C expression pattern is generalized to other mossy fiber axons partly remains a question, since single neurons innervate both aldolase C-positive and -negative bands in some mossy fiber systems such as external cuneate neurons (Ji & Hawkes, 1994) and spinocerebellar neurons (Luo et al, 2018).…”
Section: Projection Of Single Bpn Axons To Aldolase Cpositive Compamentioning
confidence: 85%
“…The present study extends this single axonal reconstruction analysis to single neurons in various parts of the BPN that project to various lobules and aldolase C compartments of the bilateral cerebellar cortices of rats. The present results obtained in the rat will be compared with those in the mouse (Biswas, Luo, Sarpong, & Sugihara, 2019).…”
mentioning
confidence: 87%
See 3 more Smart Citations